2019
DOI: 10.1177/0192623319861367
|View full text |Cite
|
Sign up to set email alerts
|

Intrarenal Renin–Angiotensin System Involvement in the Pathogenesis of Chronic Progressive Nephropathy—Bridging the Informational Gap Between Disciplines

Abstract: Chronic progressive nephropathy (CPN) is the most commonly encountered spontaneous background finding in laboratory rodents. Various theories on its pathogenesis have been proposed, but there is a paucity of data regarding specific mechanisms or physiologic pathways involved in early CPN development. The current CPN mechanism of action for tumorigenesis is largely based on its associated increase in tubular cell proliferation without regard to preceding subcellular degenerative changes. Combing through the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 249 publications
(330 reference statements)
1
10
0
Order By: Relevance
“…The CPN in mice comprises a wide spectrum of chronic degenerative renal lesions, including glomerulosclerosis, glomerular dilation, regressive changes and atrophy of tubules, increased connective tissue, and interstitial mononuclear cell infiltrates, the latter being especially common in mice. 19 In animals with advanced lesions including pelvic dilatation, the disease may constitute the major cause of death. 3 A doubled to tripled incidence of CPN has been reported in female mice versus males.…”
Section: Discussionmentioning
confidence: 99%
“…The CPN in mice comprises a wide spectrum of chronic degenerative renal lesions, including glomerulosclerosis, glomerular dilation, regressive changes and atrophy of tubules, increased connective tissue, and interstitial mononuclear cell infiltrates, the latter being especially common in mice. 19 In animals with advanced lesions including pelvic dilatation, the disease may constitute the major cause of death. 3 A doubled to tripled incidence of CPN has been reported in female mice versus males.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, vitamin D3 deficiency activates the local RAAS in the kidney, aggravating renal injury [63,64]. Intrarenal RAAS overactivation has been implicated in various animal models of renal disease as both an initial response and a driver for disease progression without increased plasma renin activity or plasma Ang II [65].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the lack of association between systemic arterial hypertension and incidence of chronic progressive nephropathy [65], our study has illuminated the feasible crosstalk of the intrarenal RAAS overactivation and oxidative stress, inflammatory, and profibrotic signaling pathways, linking MetS to nephropathy progression independently of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous investigation of glomerular nephrin expression in Crl:CD(SD) rats with minimal change disease, nephrin expression was intact, although podocyte foot processes showed effacement under electron microscopy with no apparent morphological changes observed under light microscopy 18 . In the common renal disease of rats, chronic progressive nephropathy (CPN), it has been demonstrated that albuminuria accompanied by early-stage CPN may result in less changes in glomerular permeability from the failure to reabsorb albumin from proximal tubules 19 . In humans, there have been some investigations on the reduction of nephrin expression under minor changes 10 or under other kidney diseases 14,16 .…”
Section: Discussionmentioning
confidence: 99%